Gastrointestinal Histoplasmosis Mimicking Crohn's Disease. (16th May 2021) - Shojaei, Esfandiar; Walsh, Joanna C; Sangle, Nikhil; Yan, Brian; Silverman, Michael S; Hosseini-Moghaddam, Seyed M
Abstract: Disseminated histoplasmosis is a life-threatening disease usually seen in immunocompromised patients living in endemic areas. We present an apparently immunocompetent patient with gastrointestinal histoplasmosis who was initially diagnosed with biopsy-proven Crohn's disease. Following discontinuation of anti-inflammatory drugs and institution of antifungal therapy, his gastrointestinal illness completely improved. Specific fungal staining should be routinely included in histopathologic assessment of tissue specimens diagnosed as Crohn's disease.